The impact of presurgical nasoalveolar molding on the surgical and quality of life outcome: A case report with 1-year follow-up - Fatmah Nasser Almotawah (Wolters Kluwer Medknow Publications, 2020)
Since its introduction in 1996, the use of presurgical nasoalveolar molding (P-NAM) has been a controversial topic. While P-NAM has become routine in many cleft centers, there have been others who have refused to adopt it. Difficulties cited have included the apparent lack of parent co-operation and perceived challenges in parent compliance. This report looks at both the esthetic postsurgical outcomes and the impact the procedure has on the overall oral health-related quality of life. The report looks at not only the procedure of P-NAM but also examines the steps a multidisciplinary team would need to take in order to make the experience beneficial to both the surgeon and the parent.